History of Appearing and Creation of Ukrainian Folk Doll and its Educational Potential - Siginishyna, Galyna; Abramovych, Galyna (Pedagogical Discourse, 2013)
The article studies how Ukrainian folk doll in general and reeled doll in particular appeared and was created. Plastic, ornamental, figured signs of the dolls have been mentioned. The influence of the Ukrainian folk doll onto the development and education of children has been cleared up. The way of making of the tie-knot doll and the doll made of herbs has been shown.